2008
DOI: 10.1055/s-2007-989334
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro-Untersuchung unterschiedlicher PMMA-Knochenzemente - ein erster Vergleich neuer Materialien für die Endoprothetik

Abstract: In view of these differences in material properties, the clinical data from long-term use of the bone cements Refobacin Palacos R and Palacos R + G cannot be extrapolated to the newly developed PMMA cements Refobacin Bone Cement R and Smart GHV. Before broad clinical use of these cements, prospective clinical studies using RSA or DEXA and, as a second step, statistically powerful prospective comparative studies should be performed. Until these data are available, patients in whom Refobacin Bone Cement R and Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…(2008) conducted in vitro tests of different properties between the "Palacos" cements Refobacin Palacos R and Palacos R + G and the bone cements SmartSet GHV and Refobacin BCR. Their study included handling properties, chemical analysis, and testing according to the ISO standard for acrylic bone cements.…”
Section: Discussionmentioning
confidence: 99%
“…(2008) conducted in vitro tests of different properties between the "Palacos" cements Refobacin Palacos R and Palacos R + G and the bone cements SmartSet GHV and Refobacin BCR. Their study included handling properties, chemical analysis, and testing according to the ISO standard for acrylic bone cements.…”
Section: Discussionmentioning
confidence: 99%
“…Fully cemented stems were more difficult to remove during revision and were accompanied by increased bone loss in the metaphyseal area. Furthermore, the type of bone cement appeared to be important for long-term stability of the implant [6]. …”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated a significant influence of penetration on the initial component stability in TKA [11,22,23]. Limited experimental and clinical data exist for the material properties of the Refobacin ® Bone Cement R. Kock et al [6] compared the chemical composition, handling properties, and ISO standard mechanical testing of four different bone cements in vitro. Chemical analysis showed that the copolymers in Refobacin ® Bone Cement R differed from the Palacos ® cements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to stability, however, great differences have been observed between various products and manufacturers of PMMA cement [46]. In principle, PMMA-based implants can also be preformed (see Neumann, Chap.…”
Section: Hard Tissue Replacementmentioning
confidence: 99%